2019
DOI: 10.4172/clinical-practice.1000444
|View full text |Cite
|
Sign up to set email alerts
|

Nurses pain management competency and associated factors among nurses working in public hospitals, jimma zone, oromia regional state, southwest Ethiopia

Abstract: Background: Pain management for hospitalized patient requires nurses' pain management competency. However; there is paucity of information on nurse's pain management competency in Jimma Zone public hospitals. Objective: To assess nurses' pain management competency and associated factors among nurses working in public Hospitals, Jimma zone, Oromia Regional State, South west Ethiopia. Methods: Institutional based cross-sectional study design was conducted on 310 nurses working in public hospitals, Jimma zone, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…This finding was consistent with the results of previous studies in which nurses’ perceptions about collaboration with physicians was a statistically significant predictor of their pain management in mechanically ventilated patients (Asman et al, 2019 ). Neme et al ( 2018 ) also found that nurses who had a good perception of the overall nurse–physician relationship were 2.40 times more probably to be competent in pain management for hospitalized patients, compared with nurses who had a poor perception of collaboration. High collaboration between nurses and physicians can enhance the level of teamwork in decision‐making, better solve patients’ problems and create the most suitable care plan for patients (Elsous et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consistent with the results of previous studies in which nurses’ perceptions about collaboration with physicians was a statistically significant predictor of their pain management in mechanically ventilated patients (Asman et al, 2019 ). Neme et al ( 2018 ) also found that nurses who had a good perception of the overall nurse–physician relationship were 2.40 times more probably to be competent in pain management for hospitalized patients, compared with nurses who had a poor perception of collaboration. High collaboration between nurses and physicians can enhance the level of teamwork in decision‐making, better solve patients’ problems and create the most suitable care plan for patients (Elsous et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported that nurses only used superficial language to assess pain during care routines without the explicit intention of managing postoperative pain (Bach, Forman, & Seibaek, 2018 ). Other studies have found that only 36.3% of surgical nurses in Ghana administered opioid analgesics for postoperative pain on a regular schedule (Menlah et al, 2018 ) and only 36.6% of Ethiopian nurses indicated that they had competency in pain management (Neme, Nemera, & Bekele, 2018 ). Another study assessed nurses’ pain management practices using case‐study vignette pain.…”
Section: Introductionmentioning
confidence: 99%
“…The KASRP scale was used to evaluate knowledge and attitudes regarding pain management. Demographic data and work characteristics were collected based on previous studies of factors related to pain management 17,22,23. Information regarding age, sex, educational level, work experience, work units, job titles, participation in preservice and in-service training, reading books or journals on pain and applied knowledge of pain management, the use of numeric rating tools to assess pain intensity, and the use of unit-based pain guidelines were collected 17,22,23…”
Section: Methodsmentioning
confidence: 99%
“…Chronic pain starts intermittently and progresses with the passage of time. While acute pain is rapid and it diminishes with treatment [2]. The improper management of pain can cause negative impact on the body and disturb the sleep and level of comfort of patient.…”
Section: Introductionmentioning
confidence: 99%